An Ointment Tablet from Deir el-Gebrawi - Abdel-Raziq, Abdalla (Zeitschrift für ägyptische Sprache und Altertumskunde, 2016)
Publication of an ointment tablet dating from the end of Six th Dynasty or later currently in the magazine of Shutb (close to the city of Assiut).